PT Hexindo Adiperkasa TBK Stock Price Prediction for 2026-2027 Using the Autoregressive Integrated Moving Average (ARIMA) Method: JEL Classification: C53, C58, G11, G17 - Venike Leony Suteja Putri; Tarisa Everalda Sainyakit Nanthi; Yunita Ade Irma Seran; Rizky Rivaldi Patora; Elisabet Kareth; Radian Januari Situmeang (Journal of Management and Administration Provision, 2026)
This study aims to predict the stock price of PT Hexindo Adiperkasa Tbk, listed under the ticker symbol HEXA, using the Autoregressive Integrated Moving Average (ARIMA) method in RStudio. The data used consist of monthly HEXA stock prices. Historical data from January 2021 to April 2025 were used as the model training dataset, while actual data from May 2025 to April 2026 were used as a benchmark for evaluating prediction results. The main forecasting period in this study covers May 2026 to December 2027. The research stages include data pattern identification, the Augmented Dickey-Fuller (ADF) stationarity test, differencing, ACF and PACF analysis, model selection based on AIC and BIC, parameter significance testing, diagnostic checking using the Ljung-Box test and Q-Q Plot, and accuracy measurement using MAPE, MAE, and RMSE. Based on the RStudio output, the best model is ARIMA (0,2,1), with an AIC value of 753.2217 and a BIC value of 757.0457. The accuracy results during the comparison period indicate a MAPE of 5.26%, an MAE of 268.67, and an RMSE of 398.31. The main forecasting results show that the HEXA stock price is predicted to reach 4,400 in May 2026 and 3,947 in December 2027. Although the MAPE value during the comparison period falls into the very good category according to the output table, the findings should still be interpreted cautiously because the Q-Q Plot indicates deviations in the tails of the residual distribution, and the prediction interval becomes wider over a longer forecasting horizon.